مصرف (في سبيل الله) لأعمال البر : دراسة تحليلية لمركز الزكاة في ولاية قدح (الماليزية) - Aziyah binti Mohamad Shauki (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This study aims to clarify the meaning of Fi Sabil Allah group of Zakat recipients and its relationship with charity activities. The researcher identifies the rules and regulations (dhawabit), and also priorities (al-awlawiyyat) of the charity activities that were categorized as Fi Sabil Allah. Kedah Zakat Centre has listed a number of charity activities according to the fatwa that was issued by Kedah Fatwa Centre. This thesis contributes to Kedah Zakat Centre, Kedah Fatwa Centre and also embarks as guidance to charity organizations and charity institutions. The researcher used three methods to complete the study which are observational method, analytical method, and also case study. The case study is the most important part of writing as it illustrates whether the practices of Zakat Centre in delivering of zakat property contradict or follow the theory of Islamic teaching. The researcher has submitted evidence and all the information that were gathered from Kedah Fatwa Centre and Kedah Zakat Centre through the interviews conducted. The researcher has concluded that most contemporary Muslim scholars agree to define charity activities as Fi Sabil Allah that are used to get zakat property and it is also practised by Kedah Zakat Centre. From this statement, it is clearly seen that Kedah Zakat Centre does not follow Shafie school of thought at this time. From the data analysis, Kedah Zakat Centre has donated 77% of Zakat property from Fi Sabil Allah group to education, 15% to propogating Islamic teaching, and 8% to Lembaga Tabung Haji and the rest to unclassified group. The researcher has come up with a conclusion and suggestions at the end of this thesis.